2020
DOI: 10.1111/ene.14167
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of subjective cognitive decline plus criteria in predicting the progression to Alzheimer’s disease: an 11‐year follow‐up study

Abstract: Background and purpose: Subjective cognitive decline (SCD) is a self-experienced decline in cognitive capacity with normal performance on standardized cognitive tests and has been shown to increase the risk of Alzheimer's disease (AD). SCD could also be related to other conditions such as normal aging, psychiatric, neurological or medical disorders. The SCD Initiative proposed a set of features (SCD-plus) that increase the likelihood of preclinical AD in individuals with SCD. Our aim was to assess the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Several studies applying multifactorial approaches found that demographic and genetic factors, such as age at onset [1,8], APOE ε4 genotype [8], and cognitive reserve [9][10][11], may influence the risk of progression from SCD to MCI and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies applying multifactorial approaches found that demographic and genetic factors, such as age at onset [1,8], APOE ε4 genotype [8], and cognitive reserve [9][10][11], may influence the risk of progression from SCD to MCI and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…We used Cox regression analysis to ascertain that the effect of presence of IAs on progression from SCD to MCI was independent of other covariates. We considered 60 years (as suggested by Jessen et al [10] and Mazzeo et al [25]) as the cut-off value to dichotomize age at baseline. Bonferroni correction was applied to correct for multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored the relationship of IAs with age at baseline and APOE ε4, two well‐known risk factors for objective cognitive decline and for progression to AD in patients with SCD [25]. We found that IAs further increased the risk of progression to MCI in patients who were carriers of the APOE ɛ4 allele and in patients who were older than 60 years at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has identi ed that the bene cial effect of education on cognitive function can not be modi ed by the APOE ε4 status in healthy older adults with more than 4-year period follow-up [40]. In individuals with SCD, the APOE ε4 allele signi cantly increased the risk of conversion to AD dementia [41], while at the symptomatic stage, the APOE ε4 allele accelerate progression from MCI to AD dementia only in APOE ε4 carriers [32]. However, further studies will be required to understand the mechanisms underlying the role of APOE ε4 allele in regulating the effect of education on cognition across the spectrum of AD.…”
Section: Discussionmentioning
confidence: 99%